Catalytic selective ethane dehydrogenation at low-temperature with low coke formation. Issue 38 (30th August 2022) - Watanabe, Kosuke; Higo, Takuma; Tsuneki, Hideaki; Maeda, Shun; Hashimoto, Kunihide; Sekine, Yasushi
Abstract : Catalytic ethane dehydrogenation for improving efficient production of ethylene, an extremely important chemical feedstock. Abstract : Catalytic ethane dehydrogenation (EDH) was investigated to improve the efficient production of ethylene, an extremely important chemical feedstock. The perovskite oxide YCrO3 was found to be more suitable than earlier reported catalysts because it exhibits greater activity and C2 H4 selectivity (94.3%) in the presence of steam at 973 K. This catalyst shows the highest activity than ever under kinetic conditions, and shows very high ethane conversion under integral reaction conditions. Comparison with EDH performance under conditions without steam revealed that steam plays an important role in stabilizing the high activity. Raman spectra of spent catalysts indicated that steam prevents coke formation, which is responsible for deactivating YCrO3 . Transmission IR and XPS measurements also revealed a mechanism by which H2 O forms surface oxygen species on YCrO3, consequently removing C2 H6 -derived coke precursors rapidly and inhibiting coke accumulation.